What are the powers of the soul in the writings of Philo (Circe de clásicos y modernos, 2018)
This article gives an overview on the course of an investigation into the concept of “power” (δύναμις) in Philo’s allegorical treatises. Our purpose is to analyze this network in three levels: 1) the ‘powers’ that build out the allegory of the Ark and its accessories, especially complex in the sense that, according to Philo exegesis, the five powers join to the Logos and so they correspond to the number six, as the towns which were given to the Levites, in Numbers 35.15, as cities of refuge, to which a person who has killed someone might flee; 2) the powers that collaborate with God when we read, in Genesis 1. 26, the plural “’let us make’ the man in our image, according to our likeness”, 3) the powers of the human soul and especially those of the ascetic –Jacob– represented by his two wives, Rachel and Leah.
Keywords: Philo; powers; soul; Ark; Jacob